Implementing mental health in practice : strategies to engage patients and families. Depression - Bauer, Nerissa S.; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2015)
This video focuses on using motivational interviewing techniques to identify and address depression. In the case demonstrated, a 15-year-old boy presents for a yearly physical. During the visit, he mentions feeling tired and having trouble getting up in the morning. When he is not in school, he stays alone in his room and no longer spends time with his friends.
Presenter: Nerissa S. Bauer.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 16, 2020)
Keywords: Depression in children; Depression in adolescence; Documentary films; Educational films; Nonfiction films; Internet videos; Streaming video; Short films